Indonesia Government’s Efforts to Eradicate Stunting Through the Free Nutritious Meal Program for Children: Opportunities and Challenges - Pambudi, Anggy Wira (Jurnal Politikom Indonesiana, 2024)
The problem of stunting is a problem that can threaten the realization of the vision of Indonesia Emas 2045. One of the efforts to prevent stunting is through the Free Nutritious Meals for Children program, the program is a form of stunting prevention intervention through the provision of nutritious food. In this study, researchers examine the opportunities and challenges of the program. The purpose of this study is to examine the readiness of the Free Nutritious Meals for Children program. This study was conducted using a public policy perspective, especially using policy analysis theory. The research method used is a qualitative method using secondary data. This study found that there are several opportunities and challenges in implementing the Free Nutritious Meals for Children program, such as strong parliamentary support, and several challenges such as the need for a large budget, an un-resilient food supply chain, and doubts about the effectiveness of the program. With so many challenges, the program is not ready to be implemented and has risks if implemented. Keywords: Free Nutritious Meal Program for Children, Golden Indonesia Vision 2045, Stunting